2008
DOI: 10.1016/j.bbagrm.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ubiquitination at the synapse

Abstract: The ubiquitin proteasome system (UPS) was first described as a mechanism for protein degradation more than three decades ago, but the critical roles of the UPS in regulating neuronal synapses have only recently begun to be revealed. Targeted ubiquitination of synaptic proteins affects multiple facets of the synapse throughout its life cycle; from synaptogenesis and synapse elimination to activity-dependent synaptic plasticity and remodeling. The recent identification of specific UPS molecular pathways that act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 118 publications
1
50
0
Order By: Relevance
“…Moreover, recent studies have identified several additional mammalian E3s at the synaptic site, including SCRAPPER (9), Siah (24,25), Staring (26), and Parkin (27). Although ample evidence supports the role of protein ubiquitination in synaptic development and plasticity in vertebrates (28), the specific molecular mechanisms underlying these effects remain to be elucidated.…”
Section: Cip1mentioning
confidence: 99%
“…Moreover, recent studies have identified several additional mammalian E3s at the synaptic site, including SCRAPPER (9), Siah (24,25), Staring (26), and Parkin (27). Although ample evidence supports the role of protein ubiquitination in synaptic development and plasticity in vertebrates (28), the specific molecular mechanisms underlying these effects remain to be elucidated.…”
Section: Cip1mentioning
confidence: 99%
“…Other mRNA-binding proteins, such as fragile-X mental retardation protein (FMRP), similarly have crucial roles in the regulation of synaptic mRNA stability, trafficking and translation (Gatto and Broadie, 2008;Pan and Broadie, 2007;Pan et al, 2004;Pan et al, 2008;Repicky and Broadie, 2009;Tessier and Broadie, 2008;Zhang et al, 2001;Zhang et al, 2005). Moreover, local protein degradation via the ubiquitin proteasome system (UPS) has also recently been established as a key mechanism that shapes synaptic structural development, neurotransmission strength and synaptic plasticity (Haas and Broadie, 2008;Haas et al, 2007a;Haas et al, 2007b;Speese et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…At the synapse, FMRP has several functions, including the control of axonal and dendritic arbor size, bouton number and distribution, transmission strength, postsynaptic glutamate receptor trafficking and the regulation of presynaptic vesicle pools (Gatto and Broadie, 2008;Pan and Broadie, 2007;Pan et al, 2008;Pan et al, 2004;Repicky and Broadie, 2009;Tessier and Broadie, 2008;Zhang et al, 2001;Zhang et al, 2005). In balance with translation regulation, UPSmediated degradation has dynamic functions that control synapse architecture, neurotransmission strength and synaptic protein abundance, including postsynaptic glutamate receptors (Haas and Broadie, 2008;Haas et al, 2007a;Speese et al, 2003). The ubiquitin ligase highwire acts to restrict synaptic overgrowth by down-regulating the MAPKKK-Wallenda pathway, where mutants exhibit increased neuromuscular junction (NMJ) branch and bouton numbers (Wan et al, 2000;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Active transport mechanisms exist and have been well characterized for AMPA-type glutamate receptors (AMPA-Rs) 1 via either insertion into the synapse or tighter association with the postsynaptic density (PSD) following lateral diffusion within the cell membrane (2). In addition to AMPA-Rs, other proteins known to be subject to activity-dependent regulation include calcium calmodulin-dependent protein kinase II alpha and beta, NMDA-type glutamate receptors (NMDA-Rs), and proteosome subunits (3)(4)(5). Synaptic protein content is dysregulated in a number of neuropsychiatric and neurodegenerative diseases, including Alzheimer's disease and fragile X mental retardation (6 -8).…”
mentioning
confidence: 99%